Diagnosis of Slipped Capital Femoral Epiphysis: How to Stay out of Trouble? - Vito Pavone; Gianluca Testa; Paola Torrisi; Kathryn Louise McCracken; Alessia Caldaci; Andrea Vescio; Marco Sapienza (MDPI AG, 2023)
Slipped capital femoral epiphysis (SCFE) is the most common hip disorder affecting children and adolescents aged between 9 and 16 years, affecting approximately 10 per 100,000 children per year. The diagnosis of SCFE is often delayed, leading to an increased risk of complications. This study aims to provide the latest evidence concerning the causes of diagnostic delay and risk factors for SCFE and to educate general practitioners and paediatricians to help reduce delays in diagnosis and provide earlier therapeutic intervention. A literature search was conducted in the ScienceDirect and PubMed databases according to the PRISMA statement. Suitable studies for this systematic review included 22 articles discussing the aetiology of SCFE, risk factors, and causes of late diagnosis. Causes of delayed diagnosis include underestimation by patients, initial diagnostic approach by a non-orthopaedic professional, inadequate imaging, failure to recognize morphological changes, and variation in symptomatic presentation. The underlying risk factors for SCFE are likely part of a multifactorial process which involves anatomical variations and the metabolism of leptin, growth hormone, insulin, and other metabolic parameters. This review highlights the importance of early recognition and diagnosis of SCFE and proposes an algorithm for physicians to approach children who may have this condition.